2016
DOI: 10.1039/c6cp01297c
|View full text |Cite
|
Sign up to set email alerts
|

Chromophore interactions leading to different absorption spectra in mNeptune1 and mCardinal red fluorescent proteins

Abstract: Extensive MD simulations combined with QM/MM calculations have been performed on mNeptune1 and mCardinal red fluorescent proteins to establish the reasons behind the red shift of the excitation wavelength of mCardinal with respect to mNeptune1. In both cases, it is seen that Arg197 stabilizes the chromophore but cannot be described as stabilizing preferentially the excited state because of the anchor point of the interaction. The interactions of the linking bonds to the α-helix of both proteins to the chromoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 54 publications
0
16
0
Order By: Relevance
“…We investigate the electrostatic spectral tuning in both the deprotonated (anionic) and protonated (neutral) forms of p -hydroxybenzylideneimidazolinone (pHBDI), a model compound of the fluorophore of wild-type GFP (see Figure ). Spectral tuning strategies in GFP have primarily focused on chemically modified chromophores, π-stacking, and the protonation state of the phenolate group. As a result, there have been relatively few investigations into the electrostatic spectral tuning mechanism in GFP. , A recent computational study by Kaila et al has investigated the effect of the protein on the absorption spectrum of pHBDI compared to the gas phase . They found that the protein significantly red shifts the absorption of pHBDI relative to the gas phase, and the effect is largely electrostatic.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We investigate the electrostatic spectral tuning in both the deprotonated (anionic) and protonated (neutral) forms of p -hydroxybenzylideneimidazolinone (pHBDI), a model compound of the fluorophore of wild-type GFP (see Figure ). Spectral tuning strategies in GFP have primarily focused on chemically modified chromophores, π-stacking, and the protonation state of the phenolate group. As a result, there have been relatively few investigations into the electrostatic spectral tuning mechanism in GFP. , A recent computational study by Kaila et al has investigated the effect of the protein on the absorption spectrum of pHBDI compared to the gas phase . They found that the protein significantly red shifts the absorption of pHBDI relative to the gas phase, and the effect is largely electrostatic.…”
Section: Resultsmentioning
confidence: 99%
“…98−102 As a result, there have been relatively few investigations into the electrostatic spectral tuning mechanism in GFP. 103,104 A recent computational study by Kaila et al has investigated the effect of the protein on the absorption spectrum of pHBDI compared to the gas phase. 105 They found that the protein significantly red shifts the absorption of pHBDI relative to the gas phase, and the effect is largely electrostatic.…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 99%
“…The dihedral force constants obtained with the FFTK parametrization for the four dihedral angles X-CG2R57-CG2R57-X seem to be too low. Thus, we have set them to 4.50 kcal/(mol rad 2 ), multiplicity 2, and phase 180.00°, as done by Armengol et al 20 For the dihedral angle parametrization, the maximum force constant has been set to 20 kcal/mol and the energy cutoff to 20 kcal/mol. The default maximum force constant of 3 kcal/ mol is not appropriate for our system as double bonds and rings are involved, which require a significantly larger force constant.…”
Section: ■ Computational Methodologymentioning
confidence: 99%
“…However, we assume that the qualitative picture stays the same. We performed an analysis of the shift of the natural bond orbital (NBO) charge from the GS to the ES as it has been done by Armengol et al 20 for a randomly chosen snapshot structure of the WT_0, GS, and Phot. conv.…”
Section: The Journal Of Physical Chemistry Bmentioning
confidence: 99%
See 1 more Smart Citation